Concept of PRIDE in Comic Discourse: Axiological Approach - A. I. Bochkarev (Научный диалог)
This article examines the peculiarities of the actualization of the concept of PRIDE within comic discourse from the perspective of axiological linguistics. It determines the value status of the phenomenon under consideration based on an analysis of definitions from dictionaries spanning various years and relevant literature. The study demonstrates the evolution of attitudes toward pride and arrogance within English-speaking linguistic culture. It explores the concept’s connections with related phenomena such as arrogance, vanity, and snobbery. A four-step axiological analysis is conducted to investigate the features of the actualization of the concept of PRIDE in comic discourse. The research material comprises over 70 stand-up comedy performances and 700 episodes of situational comedies. It is established that the textual actualization of the category of pride or arrogance is typically accompanied by audience laughter or off-screen laughter. The study reveals that ridicule is directed at an inflated or unwarranted self-assessment of greatness and a sense of superiority over others. Three primary types of superiority are distinguished: intellectual, physical, and social. Furthermore, it is noted that pride/arrogance is evaluated negatively either through the outcomes it produces or through the demonstration of its unwarranted manifestations. The main linguistic means for actualizing the concept of PRIDE are identified. Thus, self-assessment of greatness is realized through hyperbolization of one’s abilities, while the sense of superiority over others is represented through various linguistic devices.